CO₂ Gasification of Black Liquor Char under isothermal and dynamic conditions - Leo Bueno, Fernando; Luis Sánchez, José (Jornada de Jóvenes Investigadores del I3A, 2025)
Black liquor char was gasified under isothermal and dynamic CO₂ conditions between 800–900 °C. Gas compositions were monitored using a CO/CO₂ analyzer. Results showed that higher temperatures increased CO production due to the Boudouard reaction, confirming the strong influence of temperature on gasification behavior and char reactivity.